IMPLEMENTATION OF THE TGT COOPERATIVE LEARNING MODEL WITH THE ASSISTANCE OF ANIMATION VIDEO MEDIA TO IMPROVE STUDENTS' LEARNING OUTCOMES OF CLASS VIIIE SMPN1 WAINGAPU - Trifonia May Nggadi; Yohana Makaborang; Yohana Ndjoeroemana (Universitas Labuhanbatu, 2023)
The low student learning outcomes of SMPN 1 Waingapu motivated this research. This study aims to demonstrate how the application of the TGT cooperative learning paradigm in class VIII E of SMPN 1 Waingapu is combined with animated video content to improve student learning outcomes. This research is a classroom action research (CAR) involving 28 students in pre-cycle, cycle I, and cycle II activities. Utilizing quantitative descriptive in data analysis. While the emotive domain uses an evaluation rubric, the cognitive domain uses a pretest and posttest. Based on the findings of this study, students' science learning outcomes at SMPN 1 Waingapu can be improved with the TGT learning model with the help of animated video media. The number of students who completed 2 with a percentage of 7% obtained an average of 63 overall student learning outcomes during the pre-cycle. The cognitive component was then completed by 15 students in cycle I with a percentage of 54%, and by 13 students with a percentage of 47%. The emotional component of the first cycle has an average value of 36.5 and the average percentage is 66.7%. The results of the second cycle of student learning show. The average value of the emotional component of the second cycle is 75.5 with a high percentage of 100.0%. Thus it can be stated that the use of the TGT cooperative learning paradigm in class VIIIE of SMPN 1 Waingapu with the use of animated video media can improve student learning outcomes.Keywords: Team Games Tournament cooperative learning model, learning outcomes AbstrakRendahnya hasil belajar siswa SMPN 1 Waingapu menjadi pemicu dilakukannya penelitian ini. Penelitian ini bertujuan untuk mengkaji bagaimana penerapan paradigma pembelajaran kooperatif TGT dalam kaitannya dengan konten video animasi dapat meningkatkan hasil belajar siswa kelas VIIIE SMPN 1 Waingapu. Penelitian ini merupakan penelitian tindakan kelas (PTK) yang melibatkan 28 siswa pada kegiatan prasiklus, siklus I, dan siklus II. Menggunakan deskriptif deskriptif, menganalisis data. Sedangkan ranah emosional menggunakan rubrik evaluasi, ranah kognitif menggunakan pretest dan posttest. Berdasarkan temuan penelitian ini, hasil belajar IPA siswa di SMPN 1 Waingapu dapat ditingkatkan dengan model pembelajaran TGT dengan bantuan media video animasi. Jumlah mahasiswa yang menyelesaikan 2 mata kuliah dengan persentase 7% diperoleh rata-rata 63 total hasil belajar mahasiswa selama pra siklus. Komponen kognitif kemudian diselesaikan oleh 15 siswa pada siklus I dengan tingkat ketuntasan 54%, dan oleh 13 siswa dengan tingkat ketuntasan 47%. Komponen emosional siklus I memiliki nilai rata-rata 36,5 dan persentase rata-rata 66,7%. Hasil belajar siswa pada siklus II memiliki skor rata-rata 85 untuk seluruh siswa. Dari mereka yang menyelesaikannya, 26 orang merupakan 93% dari kelompok, sedangkan 3 siswa sisanya merupakan 7% dari kelompok. Nilai rata-rata komponen emosi siklus II sebesar 75,5 dengan persentase predikat tinggi yaitu 100,0%. Berdasarkan hal tersebut dapat disimpulkan bahwa penggunaan model pembelajaran kooperatif Team Games Tournament (TGT) yang didukung dengan media video animasi dapat meningkatkan hasil belajar siswa kelas VIII E SMP Negeri 1 Waingapu.Kata kunci: model pembelajaran kooperatif Team Games Tournament, hasil belajar.